ChemInform Abstract: Iron‐Catalyzed Synthesis of Arylsulfinates Through Radical Coupling Reaction. Issue 25 (June 2016) - Zhang, Weixi; Luo, Meiming
Abstract: A novel strategy to insert sulfonyl fragment into arenes is accomplished via an iron‐catalyzed radical coupling reaction.